Bridging the Gap: Manual and Digital Pattern-drafting in Fashion Education - Takbeer Mohiuddin; Sajid Hussain (Journal of Design and Textiles, 2025)
Pattern-drafting, a core skill in fashion design education, bridges the gap between technical garment manufacturing and creative designing. It was once taught by hand, has changed drastically with the introduction of digital technologies, such as CLO 3D and Gerber AccuMark. The current study aimed to examine the attitudes, techniques, and potential of both manual and digital pattern drawing within the context of Pakistani fashion education. Sample size included Eight instructors and 100 students out of which 92 responses were added in the study, using a mixed-methods approach, surveys and interviews were conducted at a number of institutions in Lahore, Sialkot, and Faisalabad. The findings demonstrated that although manual drawing is still preferred for foundational learning, students recognize the value of digital skills for career advancement. Institutional problems, such as inflexible curricula, poor faculty preparation, and a lack of infrastructure make it difficult to integrate digital resources. In order to prepare graduates for the rapidly changing fashion business, the study aimed to promote a hybrid curriculum model that embraces digital innovation while valuing manual workmanship.